Tectonaquinones A, B and C: three new naphthoquinone derivatives from the heartwood of Tectona grandis. Issue 7 (3rd April 2022) - Vyas, Pooja; Wadhwani, Barkha Darra; Khandelwal, Poonam; Araya, Hiroshi; Fujimoto, Yoshinori
Abstract: Chemical investigation of the chloroform extract of heartwood of Tectona grandis L. f. led to the isolation of three new naphthoquinone derivatives, tectonaquinones A (1 ), B (2 ) and C (3 ), along with six known compounds: barleriaquinone-I (4 ), tectoquinone (5 ), tecomaquinone I (6 ), lapachol (7 ), obtusifolin (8 ) and 2-hydroxy-3-methyl anthraquinone (9 ). The structures of the new compounds were elucidated by spectroscopic methods including 2 D NMR experiments. Tectonaquinone B is the first natural compound that has a hexa-cyclic dinaphthofuran-dione scaffold. Tectonaquinone C has a bicyclic acetal motif that is unusual in nature. Graphical Abstract: